2017
DOI: 10.1007/s00441-017-2743-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin affects membrane integrity, intracellular reactive oxygen species, caspase3 activity and AKT phosphorylation in frozen thawed human sperm

Abstract: Cryopreservation is known to induce oxidative stress in spermatozoa. Although melatonin has powerful antioxidant properties, little is known about its effects on human sperm quality during cryopreservation. The present study was undertaken to investigate the effects of melatonin treatment on human sperm parameters essential for fertilization. We first evaluated the effects of various concentrations of melatonin (0-15 mM) on human sperm parameters such as motility, viability and levels of intracellular reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 67 publications
3
28
0
Order By: Relevance
“…Furthermore, melatonin has been shown to improve motility and other sperm functional parameters in human, ram, equine and boar spermatozoa (reviewed in Cebri an-P erez et al, 2014). In agreement with this hypothesis, in vitro treatment of spermatozoa with melatonin decreases intracellular levels of reactive oxygen (ROS) and nitrogen species (RNS; Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Najafi et al, 2018), membrane lipid peroxidation (Gadella et al, 2008;Du Plessis et al, 2010;Da Silva et al, 2011), apoptosis markers Da Silva et al, 2011;Espino et al, 2011;Najafi et al, 2018) and DNA fragmentation (Sarabia et al, 2009). In agreement with this hypothesis, in vitro treatment of spermatozoa with melatonin decreases intracellular levels of reactive oxygen (ROS) and nitrogen species (RNS; Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Najafi et al, 2018), membrane lipid peroxidation (Gadella et al, 2008;Du Plessis et al, 2010;Da Silva et al, 2011), apoptosis markers Da Silva et al, 2011;Espino et al, 2011;Najafi et al, 2018) and DNA fragmentation (Sarabia et al, 2009).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, melatonin has been shown to improve motility and other sperm functional parameters in human, ram, equine and boar spermatozoa (reviewed in Cebri an-P erez et al, 2014). In agreement with this hypothesis, in vitro treatment of spermatozoa with melatonin decreases intracellular levels of reactive oxygen (ROS) and nitrogen species (RNS; Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Najafi et al, 2018), membrane lipid peroxidation (Gadella et al, 2008;Du Plessis et al, 2010;Da Silva et al, 2011), apoptosis markers Da Silva et al, 2011;Espino et al, 2011;Najafi et al, 2018) and DNA fragmentation (Sarabia et al, 2009). In agreement with this hypothesis, in vitro treatment of spermatozoa with melatonin decreases intracellular levels of reactive oxygen (ROS) and nitrogen species (RNS; Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Najafi et al, 2018), membrane lipid peroxidation (Gadella et al, 2008;Du Plessis et al, 2010;Da Silva et al, 2011), apoptosis markers Da Silva et al, 2011;Espino et al, 2011;Najafi et al, 2018) and DNA fragmentation (Sarabia et al, 2009).…”
Section: Introductionmentioning
confidence: 77%
“…While this conclusion could be surprising at first glance, one should note that boar spermatozoa are characterised by a very low ROS production rate, even when subjected to treatments that, such as freeze-thawing, induce the generation of high intracellular ROS in other species (Bilodeau et al, 2000;Guthrie & Welch, 2006;Yeste et al, 2013Yeste et al, , 2015a. As a consequence, in species such as equine, bovine and human, melatonin has a clear antioxidant effect and affects membrane lipid peroxidation and ROS levels (Gadella et al, 2008;Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Da Silva et al, 2011;Najafi et al, 2018). As a consequence, in species such as equine, bovine and human, melatonin has a clear antioxidant effect and affects membrane lipid peroxidation and ROS levels (Gadella et al, 2008;Rao & Gangadharan, 2008;Du Plessis et al, 2010;Jang et al, 2010;Da Silva et al, 2011;Najafi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…During full‐text screening, no common antioxidants were identified in nineteen articles (Asadmobini, Bakhtiari, Khaleghi, Esmaeili, & Mostafaei, ; Brugnon et al, ; Fontoura et al, ; Isachenko et al, ; Kotdawala et al, ; Lu et al, ; Meamar et al, ; Naeini, Bafrani, & Nikzad, ; Najafi et al, ; Oehninger, Duru, Srisombut, & Morshedi, ; Parameswari et al, ; Pariz & Hallak, ; Saeednia et al, ; Sbracia, Grasso, Sayme, Stronk, & Huszar, ; Sobhani, Eftekhaari, Shahrzad, Natami, & Fallahi, ; Taylor, Roberts, Sanders, & Burton, ; Vickram et al, ; Werner et al, ), twelve articles lacked common sperm parameters (Banihani, Agarwal, Sharma, & Bayachou, ; Branco, Garcez, Pasqualotto, Erdtman, & Salvador, ; Donnelly, McClure, & Lewis, ; Esteves, Spaine, & Cedenho, ; Gadea et al, ; Garcez et al, ; Garcez, Branco, Lara, Pasqualotto, & Salvador, ; Jenkins, Aston, & Carrell, ; Li, Lin, Liu, Xiao, & Liu, ; Minaei et al, ; Nabi et al, ; Shabani Nashtaei et al, ) and one article lacked sufficient data (Karimfar et al, ). Finally, 23 articles (Aliabadi, Jahanshahi, Talaei‐Khozani, & Banaei, ; Askari, Check, Peymer, & Bollendorf, ; Azadi, Tavalaee, Deemeh, Arbabian, & Nasr‐Esfahani, ; Bateni et al, ; Deng et al, ; Duru, Morshedi, Schuffner, & Oehninger, ; Esteves, Sharma, Thomas, & Agarwal, ; Ghorbani et al, ; Kalthur et al, ; Keshtgar, Iravanpour, Gharesi‐Fard, & Kazerooni, ; Martinez‐Soto, Dioshourcade, Gutiérrez‐Adán, Landeras, & Gadea, ; Merino et al, ; Moubasher, Din, Ali, El‐sherif, & Gaber, ; Najafi et al, ; Nekoonam, Nashtaei, Naji, Zangi, & Amidi, ; Rossi, Mazzilli, Delfino, & Dondero, ; Taylor et al, ; Thomson et al, ; Varghese et al, ; Wang, Sikka, Veeraragavan, Bell, & Hellstr...…”
Section: Resultsmentioning
confidence: 99%
“…In fact, caspase 3 is activated after thawing and alters the outer layer of the sperm plasma membrane. It was shown that caspase 3 activity was decreased in the melatonin group in comparison with the control group (Najafi et al, ). Macromolecules are protected by melatonin against OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation